Resistances in colonization scenarios: Comparative analysis of the Mapuche and Bedouin of the Negev women’s movements - Silvestri, María Agostina (Nomadías, 2022)
This work will attempt to present and develop a comparative pairing between the strategies of struggle and resistance of indigenous women, particularly Mapuche women, and Palestinian women, particularly the Bedouin of the Nagev. The main social, historical, and political conditions that delineate in each case the participation of women in resistance to colonization-occupation and in community (re) organization will be addressed. Strategies aimed at the recovery and / or visibility of Mapuche and Bedouin identities, and the struggle for the recovery of the territories and for the national liberation / self-determination of the peoples, will be particularly addressed. For these purposes, a hermeneutical analysis of bibliographic and audiovisual sources will be carried out.